Dissociative Symptoms and Disorders in Patients With Bipolar Disorders: A Scoping Review - Rajkumar, Ravi Philip (Frontiers in Psychiatry, 2022)
Dissociative disorders are an important group of trauma-related disorders associated with significant disability. The co-occurrence of dissociative disorders (DD) and symptoms (DS) in bipolar disorder has been relatively understudied, but there is some evidence that this comorbidity may have significant mechanistic and clinical implications. This paper presents the results of a scoping review of the frequency and correlates of DS and DD in bipolar disorder. Based on the available evidence, DS / DD are more common in bipolar disorder than in healthy controls or in unipolar depression, are related to childhood trauma, and are associated with psychotic symptoms, suicide attempts, and a poorer response to treatment in patients with bipolar disorder. The implications of these findings, and possible mechanistic pathways underlying them, are discussed based on the current literature. Clinicians should be aware of the frequent occurrence of significant DS or DD when treating patients with bipolar disorder. A tentative future research agenda for this field, based on clinical, risk factor-related and neurobiological considerations, is outlined.